Micro-explosion and burning characteristics of a single droplet of pyrolytic oil from castor seeds. (5th March 2017) - Chen, Guan-Bang; Li, Yueh-Heng; Lan, Ching-Hsien; Lin, Hsien-Tsung; Chao, Yei-Chin
Highlights: Castor pyrolytic oil exhibits a smaller micro-explosion than that of emulsion fuel. The residue after combustion is only 0.18% of the weight of the pyrolytic oil. Three different stages of micro-explosion are identified. During the combustion process, the variation of droplet diameter follows d 2 -law. Abstract: In the study, castor pyrolytic oil is produced from castor seeds by thermal pyrolysis and its pyrolysis reaction and oxidation reactions are investigated using thermogravimetric analysis. The results are also used to evaluate the characteristic combustion properties, such as the ignition temperature, burnout temperature and combustion characteristics index. The suspended droplet experimental system is also used to explore the micro-explosion phenomena and combustion modes of castor pyrolytic oil under different ambient temperatures. The castor pyrolytic oil is a multi-component fuel and has a complex process during the heating process and micro-explosion occurs, causing the droplet surface distortion. According to the timing and strength of the micro-explosion, there are three different stages: low intensity micro-explosion in the first stage, high intensity micro-explosion in the second stage and medium intensity micro-explosion in the final stage. After high-intensity micro-explosion occurred at 550 °C, more volatile vapors were released and the flammable mixture will formed a flame wrapping around droplets after ignition. During the droplet combustion process, the micro-explosion occurred continuously, but the droplet still maintained a sphere-like appearance. The variation of droplet size generally followed d 2 -law and the combustion rate constant is approximately 1.483 mm 2 /s.